2014
DOI: 10.6004/jnccn.2014.0081
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma Protuberans, Version 1.2014

Abstract: Dermatofibrosarcoma protuberans (DFSP) is an uncommon soft tissue tumor characterized by a relatively high risk of local recurrence and low risk of metastasis. The NCCN Guidelines for DFSP provide multidisciplinary recommendations on the management of patients with this rare disease. These NCCN Guidelines Insights highlight the addition of the Principles of Pathology section, which provides recommendations on the pathologic assessment of DFSP. Because DFSP can mimic other lesions, immunohistochemical studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…(36) DFSP has a low metastatic potential (1–5%)(37, 38); however, due to its recurrence potential, early surgical therapy is recommended. (39-43)…”
Section: Discussionmentioning
confidence: 99%
“…(36) DFSP has a low metastatic potential (1–5%)(37, 38); however, due to its recurrence potential, early surgical therapy is recommended. (39-43)…”
Section: Discussionmentioning
confidence: 99%
“…It differs from most of the soft tissue tumors because of the fact that it is indeed slowly progressive, locally aggresive tumor and has a high rate of recurrence rates after surgical treatment. DFSP is a rare tumor, its exact incidence is not known [1][2][3][4][5]. Recently it has been reported that the overall incidence of DFSP in United States is 4.1 per million person-years [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although it may arise anywhere on the body, typical site of involvement is the trunk and proximal extremities. DFSP is also an exceptional dermatological disease in that it is associated with a genetic translocation involving chromosomes 11 and 22 [t(17;22) (q22;q13)] [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…3 The standard of care is wide local excision, however, local recurrence is not uncommon and reaches 7.3% in more recent studies. 4 In more than 90% of cases, this tumor is characterized by an unbalanced t(17:22) (q22:q13) translocation, which results in the fusion of alpha chain type 1 of collagen gene (COL1A1) and platelet-derived growth factor beta gene (PDGFB). 5 The fusion protein results in constitutively active tyrosine kinase-mediated growth factor signaling.…”
Section: Introductionmentioning
confidence: 99%